Identification of quantitative trait loci influencing inflammation‐mediated alveolar bone loss: insights into polygenic inheritance of host–biofilm disequilibria in periodontitis. (30th June 2015) - Sima, C.; Cheng, Q.; Rautava, J.; Levesque, C.; Sherman, P.; Glogauer, M.
Abstract : Background and Objective: The relative contribution of genetic and environmental factors to the onset and progression of periodontitis is inconclusive. Despite the high prevalence, phenotypic heterogeneity and significant local and systemic implications of this disease, early detection and individualized therapy are problematic. Using a murine model of periodontitis in a panel of 17 recombinant inbred mice, the current study addressed the heritability of, and oral dysbiosis associated with, inflammation‐mediated alveolar bone loss (iABL), the hallmark of periodontitis. Material and Methods: Quantitative trait locus (QTL) genomics and quantitative PCR for over 99% of known murine oral microbiota were used. Results: It was found that iABL is a polygenic trait with 32.7% heritability. One suggestive QTL, nicknamed inflammation‐mediated alveolar bone loss locus (iABLL), was identified on chromosome 2. Eleven genes involved in innate immune responses and bone metabolism, particularly related to macrophage and osteoblast function, namely Etl4, Pdss1, Cobll1, 9330158F14Rik, Xirp2, Stk39, Mettl5, Metapl1, Itga6, Pdk1 and Sp3, were found in the iABLL using cis expression QTL and nonsynonymous single nucleotide polymorphism analyses. Specific oral microbiome shifts in saliva and tongue mucosa are associated with disease in this model. Conclusion: Our results indicate that complex host–biofilm interactions generate pathogenic states that extend beyond subgingival biofilms and periodontal tissues. Although no temporal relationship between the onset of iABL and microbiome changes were established, our findings suggest that host factors may be responsible for pathogenic shifts in subgingival biofilms when persistent and undisturbed.